Teaching the Beburon Dictionary in Balinese Language and Script in Salupangkang Village - Yus Aditya, I Wayan (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
The Balinese language plays a crucial role in preserving the cultural identity of the Balinese people, serving both as a means of communication and a symbol of unity. However, the challenge of maintaining the language's relevance among the younger generation is becoming increasingly apparent, particularly in transmigrant areas. The KKN Nusantara IV program seeks to address this challenge through the innovation of the "Kamus Beburon Berbahasa dan Beraksara Bali," an interactive learning medium developed using Powerpoint. This dictionary integrates visual and multimedia elements to create a dynamic and relevant learning experience, thereby enhancing children's interest in the Balinese language and script. The implementation of this dictionary in Salupangkang Village has shown positive results, with increased student engagement and understanding. This innovation demonstrates that technology-based educational approaches can be effective in preserving cultural heritage amid the waves of modernization.